2012
DOI: 10.1097/aci.0b013e328358cc0b
|View full text |Cite
|
Sign up to set email alerts
|

Inborn errors of human IL-17 immunity underlie chronic mucocutaneous candidiasis

Abstract: Purpose of review Chronic mucocutaneous candidiasis (CMC) is characterised by recurrent or persistent symptomatic infection of the nails, skin and mucosae mostly by Candida albicans. CMC is common in patients with profound primary T-cell immunodeficiency, who often display multiple infectious and autoimmune diseases. Patients with syndromic CMC, including autosomal dominant (AD) hyper IgE syndrome (HIES) and autosomal recessive (AR) autoimmune polyendocrinopathy syndrome type I (APS-I), display fewer other inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
214
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(235 citation statements)
references
References 117 publications
10
214
0
3
Order By: Relevance
“…Previous studies have suggested that anti-cytokine autoantibodies are involved in CMC pathogenesis in APECED patients [11,27,28,36]. It has been suggested that autoantibodies against cytokines, including IL-17A, IL-17F and IL-22, may underlie CMC in patients with APECED [11,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that anti-cytokine autoantibodies are involved in CMC pathogenesis in APECED patients [11,27,28,36]. It has been suggested that autoantibodies against cytokines, including IL-17A, IL-17F and IL-22, may underlie CMC in patients with APECED [11,28].…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal infections with Candida species indicate an underlying T-cell deficiency, which is most often secondary to immunosuppressive and/or chemotherapy, antibiotics, biological therapies, HIV, or other permissive circumstances. However, in rare patients, these infections present as a severe syndrome coined CMC, a primary immune deficiency in which the underlying cause is a genetic mutation affecting immune pathways essential for fungal protection [3]. Research in primary immune deficiency patients with isolated CMC has documented the crucial role of the signal transducer and activator of transcription 3 (STAT3)/retinoic acid receptor related orphan receptor C (RORC/ interleukin 17 (IL-17) pathway for protection against mucocutaneous fungal disease [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in rare patients, these infections present as a severe syndrome coined CMC, a primary immune deficiency in which the underlying cause is a genetic mutation affecting immune pathways essential for fungal protection [3]. Research in primary immune deficiency patients with isolated CMC has documented the crucial role of the signal transducer and activator of transcription 3 (STAT3)/retinoic acid receptor related orphan receptor C (RORC/ interleukin 17 (IL-17) pathway for protection against mucocutaneous fungal disease [3]. As proof of principle, it was found that the candidiasis in patients with autoimmune polyendocrinopathy candidiasis ectodermal dystrophy who suffer with autoimmunity as a result of AIRE gene mutations was linked to autoantibodies against Th-17 cytokines (IL-17A, IL-17F, and IL-22), elegantly explaining the CMC in the context of autoimmunity [4].…”
Section: Introductionmentioning
confidence: 99%
“…A prominent condition in IL-17-deficient humans is mucocutaneous candidiasis (14). IL-17 also has an established role in chronic inflammatory conditions in humans, including psoriasis (3, 15, 16).…”
mentioning
confidence: 99%